Qualitative research in action - May, Tim, 1957- (SAGE, 2002)
Rather than being a how-to book, this volume examines the ideas and practices of qualitative research in terms of their applicability for an understanding and explanation of the place of qualitative research in the social sciences.
Keywords: Social sciences -- Methodology.; Qualitative research.; Recherche qualitative.; Sciences sociales -- Méthodes qualitatives.; 70.03 methods, techniques and organization of social science research.; SOCIAL SCIENCE -- Research.; SOCIAL SCIENCE -- Methodology.; Qualitative research; Social sciences -- Methodology; Aufsatzsammlung; Feldforschung; Qualitative Methode; Kwalitatieve methoden.; Sociaal-wetenschappelijk onderzoek.; Sciences sociales -- Methodes qualitatives.; Aufsatzsammlung.